INTERPRETASI HAMKA TENTANG UMMATAN WASATAN DALAM TAFSIR AL-AZHAR - Abdur Rauf (Institut Agama Islam Negeri (IAIN) Keiri, 2019)
In addition to regulating human life individually, the Qur’an also regulates human life in community life. The presence of the Qur’an aims to create ummatan wasathan, namely people who call on goodness and prevent evil. This paper discusses Hamka’s interpretation of ummatan wasatan in the Tafsir Al-Azhar. This paper is a literature study. The author uses descriptive and analytical methods. This paper reveals that Hamka’s interpretation of ummatan wasathan in the Tafsir AlAzhar in general Hamka uses the tahlili method. The form of interpretation is more dominant using the interpretation of bi al-ra’yi. Hamka’s interpretation of ummatan wasatan is patterned by adabi ijtima’i (social society). Ummatan wasatan according to Hamka is a people who are in the middle, who do not dissolve in worldly life and do not dissolve in spirituality, and people who always take a straight path (S ira>tal Mustaqi>m). The characteristics of ummatan wasathan are: people who believe in Allah SWT, people who are just, people who have balance, people who have honesty, people who have courage, people who have wisdom, people who uphold the values of brotherhood, and people who take a straight path. The tasks of ummatan wasat an were: working on amar ma’ruf, nahi munkar, and being a witness for all humans.